2011
DOI: 10.1364/oe.19.001836
|View full text |Cite
|
Sign up to set email alerts
|

White light generation in Dy^3+-doped oxyfluoride glass and transparent glass-ceramics containing CaF_2 nanocrystals

Abstract: The radiative emission properties of the Dy3+ ions in an oxyfluoride glass and glass-ceramics have been studied for the generation of white light. The x-ray diffraction pattern of the glass-ceramics shows the formation of CaF2 fluorite-type nanocrystals in the glass matrix after a suitable thermal treatment of the precursor glass, whereas time-resolved optical measurements show the incorporation of the Dy3+ ions in the CaF2 nanocrystals. Intense white light has been observed when the samples are excited with 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Therefore, SrF 2 nanocrystals were prepared at temperatures in the T с1 -T с2 span. Increasing the annealing temperature from 580 to 640 o C produced narrower X-ray diffraction lines, and the average size of the formed SrF 2 nanocrystals calculated by Scherrer's formula increased from 20 to 37 nm, which was in a good agreement with independently obtained TEM data (as per [76], where an increase of 50 o C for the annealing temperature resulted in the growth of crystallite size from 20 to 40 nm).…”
Section: Properties Of Glass Ceramics and Methods Of Their Studyingsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, SrF 2 nanocrystals were prepared at temperatures in the T с1 -T с2 span. Increasing the annealing temperature from 580 to 640 o C produced narrower X-ray diffraction lines, and the average size of the formed SrF 2 nanocrystals calculated by Scherrer's formula increased from 20 to 37 nm, which was in a good agreement with independently obtained TEM data (as per [76], where an increase of 50 o C for the annealing temperature resulted in the growth of crystallite size from 20 to 40 nm).…”
Section: Properties Of Glass Ceramics and Methods Of Their Studyingsupporting
confidence: 86%
“…They tested numerous dopants and found that Dy 3+ and Eu 3+ ions showed practically utilizable visible emissions under UV-LED excitation at 365 nm [161]. This is in agreement with other data [76,148].…”
Section: Spectral and Luminescent Properties Of Glass Ceramicssupporting
confidence: 84%
See 1 more Smart Citation
“…The CCT can be calculated using the color coordinates by the McCamy empirical formula [33]; CCT = −449n 3 + 3525n 2 − 6823n + 5520.33 (8) where n = ( − )/( − ) is the inverse slope line and ( = 0.332, = 0.186) is the epicenter. The CCT values of singly doped Dy 3+ , co-doped Dy 3+ /Tb 3+ glasses and glassceramics are presented in Table III, and are therein compared with other reported CaF2 TGCS [34], oxyfluorosilicate glass-ceramics [25], GdSr2F7 TGCS [35] and 7GMETD1 glassceramics [36]. The color temperature of the singly Dy 3+ doped glass and glass-ceramics were found to be in the range 4500-4900 K, which is higher than the warm CCT (i.e., CCT<4000 K) [32].…”
Section: Chromaticity Coordinatesmentioning
confidence: 94%
“…During the last two decades, a considerable number of studies have been carried out on the optical properties of glass and glass ceramics with MF 2 (M= Ca, Ba and Sr) in their composition [14]. In comparison with the other fluorides, CaF 2 is more preferable due to the high transparency from 0.13 to 9.5 µm, refractive index compatibility with the aluminosilicate glass matrix and high solubility of rare-earth ions [17][18][19]. Therefore, rareearth ions doped transparent oxyfluoride glass-ceramics containing CaF 2 nanocrystals have attracted much attention and have become probable candidates for optical applications.…”
Section: Introductionmentioning
confidence: 99%